The Effect of Pre-Incision Urethral Plate Width and Glanular Width on the Outcome of Tubularized Incised Urethral plate repair surgery in Distal Penile Hypospadias, A prospective study - Galal, Mohamed; Taha, Diaa-Eldin; Elabden, Khaled Zein; Nabeeh, Hossam; Abdelbaky, Tarek (Urology Journal, 2021)
Purpose: To determine hypospadias repair's cosmetic and functional outcome concerning the urethral plate width and glanular width. Materials and Methods: A prospective study including 38 patients. The urethral plate width (UPW) was measured preoperatively. The cosmetic outcome was evaluated by hypospadias objective penile evaluation [HOPE] score, and the urinary stream evaluated functional outcome. We included boys with distal penile hypospadias and excluded recurrent cases with severe chordee. All patients were operated on by Snodgrass tubularized incised plate repair (TIP); they were followed up for one year. Success was deﬁned as slit-shaped meatus at the tip of the glans without ﬁstula. Results: The mean age of surgery was 4.5 ± 2.1 years. UPW was < 8 mm in 24 patients (63.2 %) (Group A), while 14 patients (36.8 % ) (Group B) had a UPW ≥ 8 mm. Overall, the mean ± SD of UPW was 4.84 ± 1.29 mm. The mean ± SD of GW was 9.52 ± 1.56 mm. Overall success was documented in 35/38 patients (92.1 %). No significant relation was founded between the complications and UPW of the patients (p-value = 0.7). Overall, the mean ± SD HOPE score was 39.1 ± 8.83. A significant relation was found between the cosmetic outcome of the two groups and the HOPE score (p-value = 0.02). Conclusion: The pre-incision urethral plate width and glanular width were not correlated with the TIP outcome. A better HOPE score is associated with a wide urethral plate.